Kemampuan Petani dalam Melakukan Usahatani Ikan Air Tawar di Kecamatan Polanharjo Kabupaten Klaten - Erlin Yusliana; Sapja Anantanyu; Eksa Rusdiyana (AGRITEXTS: Journal of Agricultural Extension, 2020)
This study aims to analyze: (1) How is the ability of farmers in conducting freshwater fish farming in Polanharjo District, Klaten Regency. (2) how the level of ability of farmers in conducting freshwater fish farming. The basic method of research is quantitative and qualitative with survey techniques. The research location was determined intentionally, which included Nganjat Village and Janti Village. Sampling using rondom proportional sampling technique consisted of 60 respondents of freshwater fish farmers. The results showed that: (1) the technical abilities of farmers in the medium category, managerial skills included in the medium category, and the social abilities of farmers in the medium category. (2) the level of achievement of the ability of farmers in conducting freshwater fish farming percentage of achievement 64.56%